2023
DOI: 10.1039/d2qi01459a
|View full text |Cite
|
Sign up to set email alerts
|

High proton conductivity modulated by active protons in 1D ultra-stable metal–organic coordination polymers: a new insight into the coordination interaction/ability of metal ions

Abstract: Highly proton-conductive metal-organic coordination polymers (MOCPs) have attracted a great deal of attention because of their potential application in proton exchange membrane fuel cell and electrochemical sensors. Currently, the precise...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 122 publications
0
4
0
Order By: Relevance
“…5d), leading to the contraction of the average hydrogen bond length, conducive to the transport of protons to achieve a lower E a value (Table 2). 99 Hence one can see that different E a values for Co-2PPA and Co-4PPA stem actually from the discrepancy in non-bonded (guest water molecules) and bonded modes (amino groups, R–NH 2 ).…”
Section: Resultsmentioning
confidence: 98%
“…5d), leading to the contraction of the average hydrogen bond length, conducive to the transport of protons to achieve a lower E a value (Table 2). 99 Hence one can see that different E a values for Co-2PPA and Co-4PPA stem actually from the discrepancy in non-bonded (guest water molecules) and bonded modes (amino groups, R–NH 2 ).…”
Section: Resultsmentioning
confidence: 98%
“…Hydroxides exhibit superior electrocatalytic activity compared to noble metals IrO 2 and RuO 2 . 17 However, due to the low conductivity and the cumbersome preparation process, the utilization of FeOOH catalyst is in the initial stage. 18 Three main factors influence the intrinsic property of iron(III) oxyhydroxide.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33][34][35] It is well demonstrated that proton hopping was achieved along H-bonding networks in a low-temperature proton conductor. [36][37][38] Therefore, the construction of H-bonding networks is crucial in proton conductors. To date, although the field of multifunctional materials has made great progress in meeting the demands of technological development, the construction of materials with as many properties as possible is still highly desirable.…”
Section: Introductionmentioning
confidence: 99%